Air pollution : from a local to global perspective - Fenger, Jes., editor; Tjell, Jens Christian., editor (Lyngby, Denmark : Polyteknisk ; Cambridge, UK : RSC Pub. [distributor], 2009)
Includes bibliographical references and index.